Komunikasi: Akar Sejarah dan Buah Tradisi Keilmuan - Nunung Prajarto (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
A dictum initiated by the Palo Alto group literally reads 'one cannot not communicate' allows us to examine the existence of the communication study. The biographical approach used by Rogers leads us to understand the emergence of the study pioneered by Darwin, Freud and Marx followed by the current development in the US. Nevertheless, by tracing the humanistic origins of the rhetoric tradition, there has been an unchained history between the rhetoric tradition and the print age of communication. This essay analyses the existence of the communication study through the history-biographical approach and the related researches.